An All-Fiber Curvature Sensor with High Sensitivity Based on Sphere-Shaped Misaligned Structure - Xiaowei Li; Qiangshen Chen; Mengyu Ren; Guoying Feng (Optics)
In this paper, a high-linear-sensitivity fiber curvature sensor based on the sphere-shaped misaligned structure (SSMS) with few-mode fiber (FMF) and single-mode fiber (SMF) was proposed and demonstrated. A spherical structure was prepared at one end of a few-mode fiber, which could effectively excite higher-order modes and generate interference in the misaligned cascade. When external environmental parameters changed, the resonance peaks formed by intermodal interference were displaced, and the shifts generated by different resonant peaks were also different. The experimental results show that the maximum curvature sensitivity was −2.220 nm/m−1, and the linear fitting coefficient reached up to 0.991, which is an extremely high sensitivity among wavelength-modulated curvature sensors. Meanwhile, the strain sensitivity of the sensor was as low as 7.99 pm/μ<semantics><mover accent="true">ε¯</mover></semantics>, and the temperature sensitivity was 3.958 pm/°C, which is a low temperature sensitivity and low strain sensitivity, and solves the cross-sensitivity problem. With advantages of simple manufacture, low cost, and favorable stability, the sensor is expected to be one of the best candidate instruments for measuring curvature and inclination.